Real‐world effectiveness of sofosbuvir‐based treatment regimens for chronic hepatitis C genotype 3 infection: Results from the multicenter German hepatitis C cohort (GECCO‐03). Issue 2 (9th November 2017) - Wehmeyer, Malte H.; Ingiliz, Patrick; Christensen, Stefan; Hueppe, Dietrich; Lutz, Thomas; Simon, Karl Georg; Schewe, Knud; Boesecke, Christoph; Baumgarten, Axel; Busch, Heiner; Rockstroh, Juergen; Schmutz, Guenther; et al.
Abstract : There are limited data regarding the real world effectiveness of direct acting antivirals (DAA) for the therapy of chronic genotype 3 hepatitis C virus (HCV) infection. All HCV genotype 3 infected patients from the German hepatitis C cohort (GECCO), which is a prospective database of nine German hepatitis C treatment centers, were included in the study. Three hundred forty‐two chronically infected HCV genotype 3 patients were analyzed (253 males [74.0%], mean age 47.3 years, 127 cirrhotic patients [37.1%] mostly with Child A cirrhosis, 113 treatment experienced patients [37.1%], 38 HCV/HIV co‐infected patients [11.1%]). SVR12 rates in the "intention‐to‐treat" analysis were as follows: sofosbuvir/ribavirin 69.4% (75/108), sofosbuvir/peginterferon/ribavirin 80.6% (58/72), sofosbuvir/daclatasvir ± ribavirin for 12 weeks 88.3% (53/63), sofosbuvir/daclatasvir ± ribavirin for 24 weeks 79.3% (23/29), sofosbuvir/ledipasvir ± ribavirin for 12 weeks 71.4% (10/14), and sofosbuvir/ledipasvir ± ribavirin for 24 weeks 86.7% (26/30). Forty patients were lost to follow‐up, 23 patients had a relapse, 4 patients stopped treatment prematurely and 1 patient died. Female sex ( P = 0.038) and treatment with two different DAAs ( P = 0.05) were predictors for SVR12 in the multivariate analysis. In conclusion, sofosbuvir/daclatasvir ± ribavirin for 12 weeks and sofosbuvir/ledipasvir ± ribavirin for 24 weeks are effective for the treatment of HCV genotype 3 infected patients including cirrhotic, treatment‐experienced or HIV/HCV co‐infected patients.